Penyesuaian Diri Siswa Tahun Pertama SMP Dimasa Pandemi Covid 19 - Vera Fauziah Fatah; Susi Susanti; Metia Ariyanti; Nursyamsiyah Nursyamsiyah (Poltekkes Kemenkes Jakarta III, 2021)
The transition in education from elementary school to junior high school is a difficult process for teenagers and requires adjustment. The process of adapting to teenagers is becoming increasingly difficult because they are currently faced with the Covid 19 pandemic. The complexity of the developmental task is a stressor for teenagers who are first year students in Junior High School. Self-adjustment is important in order to be able to align the needs of oneself and the situation outside of adolescents in order to get a better relationship between themselves and their environment. The failure of adolescents to make adjustments will cause problems such as irresponsible behavior and neglect of lessons, aggressive attitudes and withdrawing from association with peers. Based on this review, it is necessary to conduct a screening regarding the adjustment of adolescents in first year junior high school students during the Covid 19 pandemic. The research design method used descriptive quantitative. The sample in the study amounted to 81 respondents. The data collection technique used a questionnaire distributed via a google form link. Data analysis used univariate to describe the characteristics of respondents and students' self-adjustment. Data were analyzed with categorization scoring guidelines using frequency and percentage distributions. The results showed that 40.74% had sufficient adjustment and 59.26% had less adjustment. Efforts are needed to improve adolescent adjustment to prevent problems in adolescents.